1996
DOI: 10.1152/jn.1996.75.4.1411
|View full text |Cite
|
Sign up to set email alerts
|

Response properties of units in the dorsal cochlear nucleus of unanesthetized decerebrate gerbil

Abstract: 1. The electrophysiological responses of single units in the dorsal cochlear nucleus of unanesthetized decerebrate Mongolian gerbil (Meriones unguiculatus) were recorded. Units were classified according to the response map scheme of Evans and Nelson as modified by Young and Brownell, Young and Voigt, and Shofner and Young. Type II units have a V-shaped excitatory response map similar to typical auditory nerve tuning curves but little or no spontaneous activity (SpAc < 2.5 spikes/s) and little or no response to… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
78
1

Year Published

1998
1998
2014
2014

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 59 publications
(86 citation statements)
references
References 2 publications
7
78
1
Order By: Relevance
“…Principal cells in the DCN can also express a type III response pattern, and the inhibition observed in this study, in general, was not as extensive as what has been reported in the cat, with the majority of units expressing type III or type IV-t rather than type IV response patterns. The relative paucity of type IV units is a common finding in rodents and seems to be a genuine species difference (Davis et al, 1996;Stabler et al, 1996;Gdowski and Voigt, 1997;May, 2003). Type III units are better suited than type IV units to convey the signal information in a CMR-like paradigm, because they do not have a pronounced central inhibitory area (Shofner and Young, 1985;Spirou and Young, 1991;Nelken and Young, 1994;Young and Davis, 2002) and are therefore unlikely to get strong inhibitory input from type II cells.…”
Section: A Hypothesized Neural Circuit To Explain Cmrmentioning
confidence: 99%
“…Principal cells in the DCN can also express a type III response pattern, and the inhibition observed in this study, in general, was not as extensive as what has been reported in the cat, with the majority of units expressing type III or type IV-t rather than type IV response patterns. The relative paucity of type IV units is a common finding in rodents and seems to be a genuine species difference (Davis et al, 1996;Stabler et al, 1996;Gdowski and Voigt, 1997;May, 2003). Type III units are better suited than type IV units to convey the signal information in a CMR-like paradigm, because they do not have a pronounced central inhibitory area (Shofner and Young, 1985;Spirou and Young, 1991;Nelken and Young, 1994;Young and Davis, 2002) and are therefore unlikely to get strong inhibitory input from type II cells.…”
Section: A Hypothesized Neural Circuit To Explain Cmrmentioning
confidence: 99%
“…This recovery was seen in 11 of 15 units in the paper of Parsons et al 15 Similar responses to NN have been found in type IV units in cat by Spirou and Young. 2 This demonstrated the sensitivity of type III units in gerbils to the NNs. Thus, type III units in gerbils are capable of detecting spectral notches as do type IV units in cats.…”
Section: Response Map Scheme and Rate Vs Cutoff Frequency Plotsmentioning
confidence: 87%
“…To illustrate the functional role of type III units in the gerbil DCN, the conceptual model from Davis et al 2 was chosen (see Fig. 2).…”
Section: Conceptual Model Of Dcn Circuitrymentioning
confidence: 99%
See 2 more Smart Citations